2023
DOI: 10.1088/1755-1315/1140/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

The application of coffee husk ash to improve compaction characteristics of clay soil

Abstract: Soil stabilization is the modification process of one or more soil properties mechanically or chemically to generate an improved soil material with the appropriate engineering properties. Recently, stabilization methods utilizing commonly used stabilizing agents are becoming more costly. On the other hand, there is an increasing interest in identifying new green technologies that may be used to improve construction practices. As a result, the search for new materials and improved processes for processing local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The percentage above this value does not contribute to the MDD value. Similar trends were observed in the studies reported by Nath et al (2018), Ekinci and Aydin (2020), Sefene (2021), and Munirwan et al (2023).…”
Section: Compaction Characteristicssupporting
confidence: 90%
“…The percentage above this value does not contribute to the MDD value. Similar trends were observed in the studies reported by Nath et al (2018), Ekinci and Aydin (2020), Sefene (2021), and Munirwan et al (2023).…”
Section: Compaction Characteristicssupporting
confidence: 90%